DIAGNOSIS OF THE PALATABILITY OF FRUITS OF THREE FODDER TREES IN RUMINANTS - Rojas Hernández, Saúl; Olivares Pérez, Jaime; Quiroz Cardoso, Fredy; Villa Mancera, Abel; Cipriano-Salazar, Moises; Camacho-Díaz, Luis Miguel; Reynoso Palomar, Alejandro (Ecosistemas y Recursos Agropecuarios, 2015)
The chemical composition, in vitro dry matter (IVDMD) and organic matter (IVOMD) digestibility of the fruits of Pithecellobium dulce, Acacia farnesiana and Acacia cochliacantha were determined. A cafeteria test in calves, sheep and goats was developed to determine through consumption of dry matter and coeficient of preference the palatability of these fruits as a feed source. Crude protein and neutral and acid detergent fiber contents were higher in the A. cochliacantha fruit (p < 0.001) with 11.1, 55.0 and 38.3 %, respectively. Total phenols were higher (p < 0.001) in A. farnesiana fruit with 39.7 %. The IVDMD and IVOMD were greater (p < 0.001) in P. dulce fruit with 57.7 and 35.6 %, respectively. The P. dulce fruit was more palatable (p < 0.0001) for calves and those of A. cochliacanta for sheep and goats (p < 0.05). It is concluded that palatability was higher for A. cochliacanta and P. dulce fruits due to their chemical composition.